Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam Di Kelas VIII MTs Muhammadiyah 15 Medan - Hasibuan, Fitriyana (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of this study was to determine the effect of using the jigsaw type cooperative learning model on student learning outcomes using the jigsaw type cooperative learning model in the history of Islamic culture in class VIII-1 MTs Muhammadiyah 15 Medan. The jigsaw type of cooperative learning model is a learning model that is in accordance with Islamic cultural history subjects. Considering the subject of Islamic cultural history is a lesson that retells history in the past, so by using a jigsaw type cooperative learning model that emphasizes group discussions with each student learning their respective parts and then exchanging knowledge with their friends. This study uses quantitative methods where this type of research is experimental research. The population in this study were all students of class VIII MTs Muhammadiyah 15 Medan, while for the research sampling technique used a total sampling technique, where the entire population was used as a sample, using class VIII-1 as an experimental class using a jigsaw type cooperative learning model and class VIII-2 as a control class using conventional methods. By collecting data using documentation and tests, where the test is carried out in one ways, namely pretest and posttest. The variable of this research is the independent variable (X) is the application of the jigsaw type cooperative learning model and the dependent variable (Y) is the student learning outcomes in the history of Islamic culture. The results showed that the average experimental class student learning outcomes in the pretest was 57.5 and the posttest was 82.8. While the control class average learning outcomes on the prettest is 47.5 and the posttest is 76.78. This shows that there is a significant effect on student learning outcomes in class VIII-1 MTs Muhammadiyah 15 Medan by applying the jigsaw type cooperative learning model.